Activation of Pro-apoptotic Caspases in Non-apoptotic Cells During Odontogenesis and Related Osteogenesis - Svandova, Eva; Vesela, Barbora; Tucker, Abigail S.; Matalova, Eva (Frontiers in Physiology, 2018)
Caspases are proteases well known in the context of inflammation and apoptosis. Recently, novel roles of pro-apoptotic caspases have been reported including findings related to the development of hard tissues. To further investigate these emerging functions of pro-apoptotic caspases, the in vivo localization of key pro-apoptotic caspases (-3, -6, -7, -8 and -9) was assessed, concentrating on the development of two neighbouring hard tissues, cells participating in odontogenesis (represented by the first mouse molar) and intramembranous osteogenesis (mandibular/alveolar bone). The expression of the different caspases within the developing tissues was correlated with the apoptotic status of the cells, to produce a picture of whether different caspases have potentially distinct or overlapping non-apoptotic functions. The in vivo investigation was additionally supported by examination of caspases in an osteoblast-like cell line in vitro. Caspase-3, -7 and -9 were activated in apoptotic cells of the primary enamel knot of the first molar, however, caspase-7 and -8 activation was associated also with the non-apoptotic enamel epithelium at the same stage and later with differentiating/differentiated odontoblasts and ameloblasts. In the adjacent bone, active caspase-7 and -8 were present abundantly in the prenatal period, while the appearance of caspase-3, -6 and -9 was marginal. Perinatally, caspase-3 and -7 were evident in some osteoclasts and osteoblastic cells and caspase-8 was abundant mostly in osteoclasts. In addition, postnatal activation of caspase-7 and -8 was retained in osteocytes. The results provide a comprehensive temporo-spatial pattern of pro-apoptotic caspase activation, and demonstrate both unique and overlapping activation in non-apoptotic cells during development of the molar tooth and mandibular/alveolar bone. The importance of caspases in osteogenic pathways is highlighted by caspase inhibition in osteoblast-like cells, which led to a significant decrease in osteocalcin expression, supporting a role in hard tissue cell differentiation.